COOLING AND HEATING VENTILATION ROOM WITH PERIODIC - , А. Ф. (Municipal economy of cities. Series: «Economy science», 2013)
The process of cooling and heating the building during periodic ventilation. The equation that gives the possibility to determine the temperature in the room at any time during its cooling or heating.